The Perceived Meanings of Thailand Tourism “Pad Thai” Video Advertisement by Thais and Indonesians - May Magnolia Ongky Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
This thesis is a study about observing the perceived meanings produced by Thai and Indonesian respondents as respondents from different national identities can produce different perceived meanings. The process of analysis is that the writer analysed the differences between Thai and Indonesian respondents’ perceived meanings after finding out the perceived meanings from both of the respondents. The writer also analysed how meanings are perceived in Thailand tourism “Pad Thai” video advertisement ased Process of Signification using The Piercean Model as well as denotation and connotation. The study uses descriptive qualitative approach. The writer of this study found out several findings. The finding is that in perceiving, Thai respondents tend to relate the data with their personal experiences based on facts while Indonesians respondents’ perception tends to relate their emotion. From this study, the writer believes that the result will help readers understand the influence of national identity in perceiving meanings from an advertisement.